2015
DOI: 10.1002/nme.5153
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of explicit and semi‐explicit classes of model‐based algorithms for direct integration in structural dynamics

Abstract: Summary The ‘model‐based’ algorithms available in the literature are primarily developed for the direct integration of the equations of motion for hybrid simulation in earthquake engineering, an experimental method where the system response is simulated by dividing it into a physical and an analytical domain. The term ‘model‐based’ indicates that the algorithmic parameters are functions of the complete model of the system to enable unconditional stability to be achieved within the framework of an explicit form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…2 In subsequent studies, the authors have demonstrated the efficacy of the KRmethod in conducting large-scale real-time hybrid simulation of structures with nonlinear seismic response modification devices 3 and in simulating collapse response of reinforced concrete (RC) frame structures. The proposed family of algorithms, referred to as the KR-method, features an explicit formulation, unconditional stability, and controllable numerical energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In subsequent studies, the authors have demonstrated the efficacy of the KRmethod in conducting large-scale real-time hybrid simulation of structures with nonlinear seismic response modification devices 3 and in simulating collapse response of reinforced concrete (RC) frame structures. The proposed family of algorithms, referred to as the KR-method, features an explicit formulation, unconditional stability, and controllable numerical energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…2 In subsequent studies, the authors have demonstrated the efficacy of the KRmethod in conducting large-scale real-time hybrid simulation of structures with nonlinear seismic response modification devices 3 and in simulating collapse response of reinforced concrete (RC) frame structures. 4 The authors have also assessed the numerical characteristics of similar model-based algorithms 2 and developed a modified formulation to improve the overshoot and nonlinear stability characteristics of the KR-method. 5 The authors would like to thank Dean J. Maxam and Prof. Kumar K. Tamma (hereafter the Discussers) for their interest in the KR-method.…”
Section: Introductionmentioning
confidence: 99%
“…To fill the gap, Chen and Ricles developed an explicit unconditionally stable CR algorithm primarily for applications in RTHS. Kolay and Ricles theoretically analyzed the reason why the CR algorithm possesses the two great features: explicit formulation and unconditional stability. According to Kolay and Ricles, the CR algorithm is a particular case of model‐based integration algorithms, which indicates that model‐based algorithmic parameters should be predefined prior to the integration process.…”
Section: Introductionmentioning
confidence: 99%
“…Kolay and Ricles theoretically analyzed the reason why the CR algorithm possesses the two great features: explicit formulation and unconditional stability. According to Kolay and Ricles, the CR algorithm is a particular case of model‐based integration algorithms, which indicates that model‐based algorithmic parameters should be predefined prior to the integration process. The CR algorithm has been successfully applied in a number of RTHS …”
Section: Introductionmentioning
confidence: 99%
“…The commonly referenced explicit algorithm is Central Difference Method (CDM) (ref), CDM is easy to use, but it is only conditionally stable. Many new explicit methods which are unconditionally stable [17][18][19] have been developed. Though these methods are unconditionally stable, they require multiple steps which are not as efficient as the CDM.…”
Section: Introductionmentioning
confidence: 99%